Digitalization and the “Too Big to Fail” dilemma: mechanisms and asymmetric effects of banks’ Fintech innovation on total factor productivity - Li, Chengming; Zhang, Yuan; Yu, Hongwei (Technological and Economic Development of Economy, 2024)
Fintech is driving the revolution of finance and profoundly affecting the development of the financial sector. However, few studies examined how commercial banks’ fintech innovation affects total factor productivity (TFP). To build up the fintech index of commercial banks, we use web crawler technology to accumulate news related to the fintech innovation of commercial banks in Baidu news. We use the panel data of 72 banks in China from 2010 to 2020 to explore the impacts and mechanisms of fintech on commercial banks’ TFP. The results show that fintech innovation effectively improves TFP after a series of robustness tests. Further, we find that fintech innovation can improve commercial banks’ TFP by promoting innovations of financial products, increasing risk control capability, reducing cost, and improving profit. Also, the utility of fintech is more significant in banks with more assets, facilities, and human capital, which means that fintech innovation creates a “bigger is better” mindset. Meanwhile, the result of quantile regression shows that the higher the fintech innovation, the more significant the increase in TFP, which further reveals that there is ‘too big to fail’ among commercial banks under digitalization.